Wear Analysis of a Ti-5Al-3V-2.5Fe Alloy Using a Factorial Design Approach and Fractal Geometry - El-Morsy, A. W. (Engineering, Technology & Applied Science Research, 2018)
This paper describes the application of the full factorial experimental design technique to confirm the significance of the factors affecting the wear behavior of a recycled Ti-5Al-3V-2.5Fe alloy with a minimum number of experiments. The fractal theory has been used to describe the worn surface state and to investigate the relationship between the fractal dimensions and the surface morphology. The experiments of the sliding wear have been performed under stresses in the range of 1-5 MPa and within sliding velocities range of 0.2–2.0 m/s. Morphology of the worn surfaces investigations has been undertaken using a scanning electron microscope. From the analysis of variance and the nonlinear regression model, the results show that the applied stress has a higher contribution to the wear rate than the sliding velocity.